A monoclonal antibody against CD86 and its protection in a murine lupus nephritis model of chronic graft-versus-host disease. (3rd September 2017) - Han, Lianhua; Shen, Lijun; Zhu, Ying; Qiu, Yuhua
Abstract: Context: Lupus nephritis is the most common complication that causes the death of systemic lupus erythematosus patients. CD28/CTLA4 and their ligands CD80 or CD86 costimulatory pathway play a pivotal role in autoimmune disease and organ transplantation. Objectives: We generated a monoclonal antibody (clone 1D1) against human CD86 (1D1) that could recognize both human and mouse CD86, and blocked the CD86/CD28 costimulatory pathway with our mAb on a murine lupus nephritis model induced with chronic graft-versus-host disease (cGVHD). Materials and methods: Experimental lupus nephritis mice were induced with cGVHD, and splenocyte population were analyzed by flow cytometry. Autoantibodies and proteinuria were detected to evaluate the severity of lupus nephritis. The change of histopathology was observed by microscopy, fluorescence microscopy and electron microscopy. Results: we successfully generated a monoclonal antibody against human CD86(1D1). 1D1 mAb could recognize not only human CD86, but also mouse CD86. 1D1 was applied to the cGVHD-induced experimental lupus nephritis model, and our study found the production of ANA and anti-dsDNA in the 1D1-treated group was lower than those in IgG-treated group after four weeks. The pathological injure of kidney in the 1D1-treated group was lighten than that in IgG-treated group. Discussion and conclusions: Our data showed that blockade of CD86/CD28 with 1D1 induced a significant remission of proteinuria, production of autoantibodies, immune complex deposition and renal parenchyma lesions in experimental mice. Anti-CD86 Abs might be a potential method for immune therapy in autoimmune diseases and transplantation.